2001
DOI: 10.1143/jjap.40.1794
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Very Small Aperture Laser (VSAL) from a Commercial Edge Emitting Laser

Abstract: In this paper we report a method for producing very small aperture lasers (VSALs) from low-cost, commercial index guided edge emitting diode lasers. The detailed fabrication procedure is provided and the VSALs are characterized. Both high power and high aperture power to background noise power ratio are obtained even with a small aperture. This fabrication method can be applied to most commercial diode lasers without knowledge of the detailed geometry and is highly reproducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…This phenomenon was previously reported in Ref. 3 where we found that slit apertures have an effective height that is more or less defined by the extent of the optical mode width rather than the height of the aperture. This result is consistent with the manufacturer provided data and is about 0.2 m.…”
Section: B Aperture Shape Effect On the Power Of Vsalsupporting
confidence: 84%
See 1 more Smart Citation
“…This phenomenon was previously reported in Ref. 3 where we found that slit apertures have an effective height that is more or less defined by the extent of the optical mode width rather than the height of the aperture. This result is consistent with the manufacturer provided data and is about 0.2 m.…”
Section: B Aperture Shape Effect On the Power Of Vsalsupporting
confidence: 84%
“…1 Previously, we reported on a method of fabricating VSALs from commercial edge emitting lasers. 3 In principle, the final aperture size primarily determines the recording mark size. With high resolution FIB etching, an aperture size of 10 nm is achievable.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, if the diameter is smaller than λ/2, the aperture does not support propagating modes, and the transmittance is then small (tunneling is necessarily part of the transmission mechanism). Consequently, the output power through the small aperture is so weak that it cannot be applied to read or write data on a CD or DVD [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many papers have been published about the devices. Researchers have tried to make such devices with high output power by employing semiconductor edge emitting lasers or vertical cavity surface emitting lasers [2][3][4]. They changed the shape of the small aperture [5], the wavelength of incident light [6], and the material filled in the small aperture [7], etc.…”
Section: Introductionmentioning
confidence: 99%